Securing industrial control system environments: the missing piece. Issue 3 (2nd October 2018) - Ani, Uchenna D.; Daniel, Nneka; Oladipo, Francisca; Adewumi, Sunday E.
ABSTRACT: Cyberattacks on industrial control systems (ICSs) are no longer matters of anticipation. These systems are continually subject to malicious attacks without much resistance. Network breaches,  data theft, denial of service, and command and control functions are examples of common attacks on ICSs. Despite available security solutions, safety, security, resilience, and performance require both private public sectors to step-up strategies to address increasing security concerns on ICSs. This paper reviews the ICS security risk landscape, including current security solution strategies in order to determine the gaps and limitations for effective mitigation. Notable issues point to a greater emphasis on technology security while discounting people and processes attributes. This is clearly incongruent with; emerging security risk trends, the biased security strategy of focusing more on supervisory control and data acquisition systems, and the emergence of more sector-specific solutions as against generic security solutions. Better solutions need to include approaches that follow similar patterns as the problem trend. These include security measures that are evolutionary by design in response to security risk dynamics. Solutions that recognize and include; people, process and technology security enhancement into asingle system, and addressing all three-entity vulnerabilities can provide a better solution for ICS environments.